CHARTING FINANCIAL SUSTAINABILITY IN TURKEY: ANCHORED PROSPERITY IN CHANGE - Kaya , Elif Deniz; Yılmaz, Ahmet Serdar (Economics and Statistics Research Journal (ESRJ), 2024)
In the contemporary global economy, characterized by free market systems and heightened by globalization and technological advancements, the economic balances of both developed and emerging nations have been significantly influenced. These economic imbalances are not uniform across countries; they vary between developed and developing economies. Maintaining macroeconomic balance has become a crucial aspect for these nations, not just in achieving initial equilibrium but also in sustaining it over time. The concept of sustainability emerges as a critical factor in preserving this macroeconomic balance. This paper explores the implications of globalization and technological progress on economic balances, highlighting the importance of sustainability in maintaining macroeconomic stability across different economies